Comparative Analysis of Evidence Law Within the Civil Process Comparative-legal Research - Barnabishvili, Sophio (Journal of Legal Studies, 2023)
The article discusses the types of evidence used in the civil law process. Comparative-legal research includes a list of types of evidence used in the civil law process in different countries of the world, their description, and legal significance based on local law. The Code of Civil Procedure is a legal means of protecting the civil rights and freedom of a person. Proceedings are conducted in compliance with the principles of disposition and competition, which allows disputing parties, under equal conditions, to determine the essence of the dispute on their initiative and to present relevant different types of evidence to determine the truth in the case. In general, asserting one’s position, truth, or justice and obtaining, collecting and presenting relevant evidence for the purpose is related to the legal awareness, good faith and sound logic developed by the party (its representative or third parties). In the process of development of a democratic state, much attention is paid to the pursuit of perfection of individual disciplines of private law, which mainly includes the objective protection of human rights and legal interests. In this process, it is of the utmost importance that the relevant norms of the law allow the interested person to present appropriate evidence to confirm the violation of the right and request the restoration of the violated rights in the justice implementing Agency. The Code of Civil Procedure is a legal means of protecting the civil rights and freedom of a person. Proceedings are conducted in compliance with the principles of disposition and competition, which allows disputing parties, under equal conditions, to determine the essence of the dispute on their initiative and to present relevant different types of evidence to determine the truth in the case.